Reduced risk of colorectal cancer up to 10 years after screening, surveillance, or diagnostic colonoscopy - Brenner, Hermann; Chang-Claude, Jenny; Jansen, Lina; Knebel, Phillip; Stock, Christian; Hoffmeister, Michael (Gastroenterology, 2014)
Background & Aims - Data from randomized controlled trials on the effects of screening colonoscopies on colorectal cancer (CRC) incidence and mortality are not available. Observational studies have suggested that colonoscopies strongly reduce the risk of CRC, but there is little specific evidence on the effects of screening colonoscopies. - Methods - We performed a population-based case-control study of 3148 patients with a first diagnosis of CRC (cases) and 3274 subjects without CRC (controls) from the Rhine-Neckar region of Germany from 2003 to 2010. Detailed information on previous colonoscopy and potential confounding factors was collected by standardized personal interviews. Self-reported information on colonoscopies and their indications was validated by medical records. We used multiple logistic regression to assess the association between colonoscopy conducted for specific indications within the past 10 years and risk of CRC. - Results - A history of colonoscopy was associated with a reduced subsequent risk of CRC, independently of the indication for the examination. However, somewhat stronger associations were found for examinations with screening indications (adjusted odds ratio [OR] 0.09, 95% confidence interval [CI] 0.07-0.13) than for examinations with diagnostic indications, such as positive fecal occult blood test result (OR, 0.33; 95% CI, 0.19-0.57), surveillance after a preceding colonoscopy (OR, 0.33; 95% CI, 0.24-0.45), rectal bleeding (OR, 0.28; 95% CI, 0.20-0.40), abdominal symptoms (OR, 0.15; 95% CI, 0.10-0.21), or other (OR, 0.21; 95% CI, 0.14-0.30). Colonoscopy was also associated with a reduced risk of cancer in the right colon, regardless of the indication, although to a smaller extent than for other areas of the colon (OR for screening colonoscopy, 0.22; 95% CI, 0.14-0.33). - Conclusions - In a population-based case-control study, the risk of CRC was strongly reduced up to 10 years after colonoscopy for any indication. Risk was particularly low after screening colonoscopy, even for cancer in the right colon.
Online 5 September 2013
Gesehen am 22.09.2020